CONTENT BASED IMAGE RETRIEVAL MENGGUNAKAN GLCM DAN COLOR ANGLOGRAM - Livia Ashianti (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2018)
The growth of multimedia data nowadays become faster both the size and number, so it is required search tools to searching multimedia data, especially images. Image search is usually done by using keywords, but many weaknesses when searching image using keyword. so, it is required image search techniques based on the content of an image, it is known Content Based Image Retrieval (CBIR). Content Based Image Retrieval (CBIR) is an image retrieval technique from a large image database by performing feature analysis of images. To improve the retrieval capability, this paper will conduct CBIR research using color features with color anglogram and texture features with Gray Level Co-Occurrence Matrix (GLCM). The results of the experiment conducted 10 times obtained the average precision 0.813 and the average best precision is 0.828571 obtained in experiment to 3.